ANALISIS PRODUK PEMBIAYAAN ARRUM BPKB DALAM MENINGKATKAN USAHA MIKRO NASABAH - Awaluddin, Awaluddin; Eka, Novianti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research is motivated by the problems of micro-entrepreneurs who have limited capital to improve the business they are running. These problems can result in delays in business development. Then look at the increase in business being run by micro customers after receiving Arrum BPKB financing at PT Pegadaian Syariah Alaman Bolak. The indicators used as measurements of increasing a business are business assets, business income, and workforce. The formulation of the research problem is the background of the community using BPKB arrum product services, then the mechanism for BPKB arrum financing products at PT Pegadaian Syariah Alaman Bolak, and increasing customer micro businesses after obtaining BPKB arrum financing at PT Pegadaian Syariah Alaman Bolak. The theory presented in this study relates to financing products, financing functions, financing as a tool of international relations, BPKB arrum, benefits and terms of financing BPKB arrum, and micro-enterprise theory along with MSME criteria. This research is a qualitative research with a descriptive method of data sources used are primary data and secondary data. While the data collection techniques of this study were interviews, observation and documentation, the sampling technique used purposive sampling and snowball sampling. The results of this study concluded that after customers received Arrum financing, the average customer profit increased per month above the initial capital of the customers. Of the 10 customers who did Arrum financing at PT Pegadaian Syariah Alaman Bolak, their profits increased. They use Arrum's financing funds for business capital and not for consumptive needs, while they use the profit from the sale of their business for future needs. they are limited working capital, in addition to that, human resource management also needs to be improved because the average entrepreneur's education is a high school graduate. it can be concluded that Arrum's financing has a major influence on micro entrepreneurs, especially for lower and middle micro entrepreneurs.